2011
DOI: 10.1097/ta.0b013e3181fc607a
|View full text |Cite
|
Sign up to set email alerts
|

Initiating Safe Oral Feeding in Critically Ill Intensive Care and Step-Down Unit Patients Based on Passing a 3-Ounce (90 Milliliters) Water Swallow Challenge

Abstract: Successfully recommending specific oral diets for ICU and SDU patients based on passing a 3-oz water swallow challenge was supported. Importantly, when a simple bedside 3-oz challenge administered by a trained provider is passed, specific diet recommendations can be made safely and confidently without the need for further objective dysphagia testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
5
25
1
Order By: Relevance
“…The same wording applies to the 110 participants not given puree consistency on FEES. Our study design and methodology remained the same [2,3,5,9], and the validity of the 3-ounce water swallow challenge protocol to both determine aspiration risk and make safe and successful diet recommendations has not been compromised [6][7][8].We are continuing our programmatic line of research in order to corroborate our results with blinded testing, correlating oral mechanism findings with aspiration risk, and collecting longitudinal data regarding success of diet recommendations all based on the 3-ounce water swallow challenge protocol. We are confident that our research and recommendations to improve patient care by fostering safer swallowing will stand the test of time.…”
supporting
confidence: 68%
“…The same wording applies to the 110 participants not given puree consistency on FEES. Our study design and methodology remained the same [2,3,5,9], and the validity of the 3-ounce water swallow challenge protocol to both determine aspiration risk and make safe and successful diet recommendations has not been compromised [6][7][8].We are continuing our programmatic line of research in order to corroborate our results with blinded testing, correlating oral mechanism findings with aspiration risk, and collecting longitudinal data regarding success of diet recommendations all based on the 3-ounce water swallow challenge protocol. We are confident that our research and recommendations to improve patient care by fostering safer swallowing will stand the test of time.…”
supporting
confidence: 68%
“…We are not aware of any published WST study using either single or consecutive sips that has identified medical complications. 36,43,44,48,52,55,56,58,59 However, several studies either warn to avoid large volume consecutive sips in specific patient populations (eg, patients with head and neck cancer, patients with tracheostomy tube) 56,67 or excluded these patients from participation. 48,49 Second, there were three readily observable, clinical responses used to identify aspiration in the WSTs: (1) airway response, (2) voice change, and (3) either airway response or voice change.…”
Section: Discussionmentioning
confidence: 99%
“…• Importantly, when the Yale Swallow Protocol was passed, a 100 % success rate with subsequent oral alimentation was observed (Leder et al 2011b;2012a, b).…”
Section: Summary Pointsmentioning
confidence: 95%
“…To wit, aspiration risk was determined with 96.5 % sensitivity, 97.9 % negative predictive value (Suiter and Leder 2008), and a <2 % false-negative rate (Leder et al 2011b). Importantly, when the protocol was passed, a 100 % success rate with subsequent oral alimentation was observed (Leder et al 2011b;2012a, b).…”
Section: Guidelines and Protocols Criteria For A Successful And Reliamentioning
confidence: 99%
See 1 more Smart Citation